(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Managing multiple toll booths is a very complicated task. The system here is a smart Card based tollbooth system that is monitored using IoT. The Internet server maintains all the data of user accounts and also their balance. All vehicle owners would possess an RFID (Radio Frequency Identification) based card that stores their RFID number. The system at toll booths will monitor the cards scanned when a car arrives at the tollbooth. The system then connects to the online server to check if the card is valid and if valid what is the balance. If user balance is sufficient, the toll amount is deducted online and web system sends signal back to the card scanner system that the user has been billed. On receiving this signal the system operates a motor to open the toll gate for that car. The system is controlled by a microcontroller to achieve this purpose. The microcontroller uses Wi-Fi connection to connect to the internet through which system interacts with web server to perform the online verification process. Also system allows to store data of all the vehicles passed at particular time intervals for later reference and surveillance. This system thus automates the entire tollbooth billing and monitoring process with ease using RFID plus IoT based system.